The First Visibility of Crescent Moon in Thailand during the Year 2010-2022 - Chetae, Firdaow; Rassamesard, Areefen; Matcha, Sukanya; Chehlaeh, Nareemas (YRU Journal of Science and Technology, 2024)
This research aims to compare the results of the first visibility of the crescent moon carried out in Thailand over the past 13 years, from 2010 to 2022 by the Sheikhul Islam Office, with various astronomical models, to calculate the average values of astronomical parameters related to practical crescent moon observations in Thailand, and to compare those astronomical parameters obtained from Thailand with different crescent visibility criteria. This study includes 72 data of the first crescent moon visibility out of 153 lunar observations, and additional data from astronomical software (Stellarium and the Accurate Time). The analysis revealed that the average age of the crescent was 16 ± 7 hours, with an average altitude was 3.4 ± 2.7 degrees. The average elongation angle between the sun and the moon was 8.7 ± 3.8 degrees, and the crescent’s brightness was 0.69 ± 0.67%. However, it was also found that crescent observation data were inconsistent with the astronomical principles, with reported sightings of the crescent moon on the day when the moon sets before sunset accounting for 1.39% of the total data. Upon comparing the results of crescent observations in Thailand with various crescent visibility criteria, it was found that our data corresponds to the criteria of Yallop (1997), MABIMS (2016), and Odeh (2004), with percentages of 1%, 39%, and 66% of the total data, respectively. Furthermore, the percentage difference in crescent brightness from this research closely matches the values reported from Malaysia, accounting for 28%. The results of the first visibility of the crescent moon in Thailand from this research can be used as a reference database to develop crescent moon visibility criteria in Thailand, improving the accuracy of determining the first day of the new month for the Hijri (Islamic) calendar. The research is the first work to report statistical data on the first visibility of the crescent moon in Thailand.